A validated computational framework to evaluate the stiffness of 3D printed ankle foot orthoses. Issue 8 (11th June 2019) - Ielapi, Alessio; Lammens, Nicolas; Van Paepegem, Wim; Forward, Malcolm; Deckers, Jan Patrick; Vermandel, Miguel; De Beule, Matthieu
Abstract: The purpose of this study was to create and validate a standardized framework for the evaluation of the ankle stiffness of two designs of 3D printed ankle foot orthoses (AFOs). The creation of four finite element (FE) models allowed patient-specific quantification of the stiffness and stress distribution over their specific range of motion during the second rocker of the gait. Validation was performed by comparing the model outputs with the results obtained from a dedicated experimental setup, which showed an overall good agreement with a maximum relative error of 10.38% in plantarflexion and 10.66% in dorsiflexion. The combination of advanced computer modelling algorithms and 3D printing techniques clearly shows potential to further improve the manufacturing process of AFOs.